2017
DOI: 10.1007/s10554-017-1082-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of biventricular systolic strain derived from the two-dimensional and three-dimensional speckle tracking echocardiography in lymphoma patients after anthracycline therapy

Abstract: The aim of this study was to investigate the usefulness of three-dimensional (3D) speckle tracking echocardiography (STE) for assessment of both left and right ventricular systolic function in patients with lymphoma after anthracycline chemotherapy, compared with two-dimensional (2D) STE. Totally eighty-nine patients undergoing anthracycline containing chemotherapy were studied. Echocardiographic assessment included 2D and 3D left ventricular (LV) global longitudinal strain (GLS), global circumferential strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 47 publications
3
27
0
13
Order By: Relevance
“…A number of foreign research results show that LVEF values were not significantly reduced when the average cumulative dose of anthracycline was up to 350-700 mg/m 2. [16][17][18] In our study, LVEF was significantly reduced when the cumulative dose of anthracycline was at 320 mg/m 2 . Previous studies on the sensitivity of GLS in monitoring anthracycline-induced myocardial damage showed that when the average cumulative dose was 60 mg/m 2 , GLS did not decrease significantly, 19 and when the average cumulative dose was 266 mg/m 2 (200-298 mg/m 2 ), GLS decreased significantly.…”
Section: Discussionsupporting
confidence: 48%
“…A number of foreign research results show that LVEF values were not significantly reduced when the average cumulative dose of anthracycline was up to 350-700 mg/m 2. [16][17][18] In our study, LVEF was significantly reduced when the cumulative dose of anthracycline was at 320 mg/m 2 . Previous studies on the sensitivity of GLS in monitoring anthracycline-induced myocardial damage showed that when the average cumulative dose was 60 mg/m 2 , GLS did not decrease significantly, 19 and when the average cumulative dose was 266 mg/m 2 (200-298 mg/m 2 ), GLS decreased significantly.…”
Section: Discussionsupporting
confidence: 48%
“…6 It can evaluate myocardial mechanics accurately and satisfactorily. 6 Four-dimensional (4D) STE acquires a three-dimensional image of the heart and aims at real-time visualization of variation of strain in each segment of the LV employing color mapping; 6 avoids the inherent shortcomings of two-dimensional (2D) STE such as geometric structure hypothesis, time-consuming examination, and missing tracking while speckles move out of the scanning area; 7 and provides a noninvasive method to the assessment of slight damage in HFpEF comparatively simply. 8 In complete blood count analysis, red cell distribution width (RDW) has been a widely used hematological index in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 25% untwist was related to oxygen uptake, which can be used as an independent predictor of aerobic exercise ability and a good indicator of cardiac diastolic function in patients with HF . 3D‐STE can also detect early left ventricular dysfunction caused by hypertrophic cardiomyopathy, essential hypertension, type 2 diabetes mellitus, and chemotherapy drugs . In addition to evaluating LV myocardial motion, 3D‐STE can also evaluate the left atrium, right atrium, and right ventricle …”
Section: D‐ste In Assessing Myocardial Motionmentioning
confidence: 99%
“…36 3D-STE can also detect early left ventricular dysfunction caused by hypertrophic cardiomyopathy, 37 essential hypertension, 38 type 2 diabetes mellitus, 39 and chemotherapy drugs. 40 In addition to evaluating LV myocardial motion, 3D-STE can also evaluate the left atrium, 41 right atrium, 42…”
Section: Assessing Myocardial Motor Functionmentioning
confidence: 99%